Pengaruh Frekuensi Penyiraman Air Terhadap Pertumbuhan Dan Hasil Tanaman Caisim (Brassica juncea L.) Varietas Tosakan - Sardiman Sardiman; Yudhi Mahmud; Faisal Al Asad; Pandu Sumarna; Didi Carsidi (Jurnal Agro Wiralodra, 2026)
Caisim is a type of leaf vegetable from the Brassicaceae family. The availability of water greatly determines the success of plants to grow and produce. To ensure water availability is maintained, it is necessary to regulate the frequency of watering. The aim of this research is to get the correct frequency of watering for the highest growth and yield of Tosakan variety caisim plants. This research was carried out in the yard of Patrol Lor Village, Jl. Sea, Patrol District, Indramayu Regency, West Java with land height of 3 meters above sea level (masl). This research was carried out in the 2024 dry season for three months, starting from April to June 2024. The research method used was an experimental method using a one-factor Randomized Group Design (RGD), namely the frequency of watering, consisting of 8 levels and 4 replications. The 8 levels applied are A = once a day, morning and evening; B = once a day, morning; C = once a day, afternoon; D = once a day, afternoon; E = two days a day, morning and evening; F = two days, morning; G = two days, afternoon; and H = two days, afternoon. The results of the research showed that there was no effect of watering frequency on the growth and yield of Tosakan variety caisim (Brassica juncea L.) plants.